(untitled) (Al-Qamar, 2020)
Resolving apparent contradictions in Qur’ānic verses has been a very important subject in Qur’ānic sciences. Various scholars, including commentators of the Quran have worked in this field. This article highlights al-Ālūsī’s effort in this regard, which he has made in his celebrated commentary named Rūḥ al-Maʻānī. It finds that al-Ālūsī, applying different principles of Qur’ānic sciences like Asbāb al-Nuzūl, Nāsikh and Mansūkh, ʻĀm and Khāṣ, Mutlaq and Muqayyad etc. beautifully offers the solutions for apparent contradictions in the Qur’ānic Verses.